The Lord's Supper in Corinth in the context of Greco-Roman private associations - Lee, Jin-hwan (Lexington Books/Fortress Academic, 2018)
"This book examines the social dynamics of banqueting practice in Greco-Roman private associations. In so doing, the author attempts to understand how social conflicts occurred at communal banquet meetings in the Corinthian Christ group (1 Cor 11:17-34) within its own social settings"--